2008
DOI: 10.1371/journal.pntd.0000330
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Chaos of Polymorphic Mucins in a Metazoan Parasite (Schistosoma mansoni) Interacting with Its Invertebrate Host (Biomphalaria glabrata)

Abstract: Invertebrates were long thought to possess only a simple, effective and hence non-adaptive defence system against microbial and parasitic attacks. However, recent studies have shown that invertebrate immunity also relies on immune receptors that diversify (e.g. in echinoderms, insects and mollusks (Biomphalaria glabrata)). Apparently, individual or population-based polymorphism-generating mechanisms exists that permit the survival of invertebrate species exposed to parasites. Consequently, the generally accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
98
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 73 publications
9
98
0
1
Order By: Relevance
“…At present, however, there is relatively little empirical evidence demonstrating reciprocal molecular adaptations in both host and parasite. Here, we investigated the interaction between S. mansoni and the snail, B. glabrata, as this interaction is a popular model for the study of co-evolutionary dynamics Bouchut et al, 2008;Roger et al, 2008a;Roger et al, 2008b;Roger et al, 2008c;Steinauer, 2009). We confirmed that there are different levels of compatibility between two geographic strains of S. mansoni and their sympatric snail hosts, B. glabrata (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…At present, however, there is relatively little empirical evidence demonstrating reciprocal molecular adaptations in both host and parasite. Here, we investigated the interaction between S. mansoni and the snail, B. glabrata, as this interaction is a popular model for the study of co-evolutionary dynamics Bouchut et al, 2008;Roger et al, 2008a;Roger et al, 2008b;Roger et al, 2008c;Steinauer, 2009). We confirmed that there are different levels of compatibility between two geographic strains of S. mansoni and their sympatric snail hosts, B. glabrata (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are equipped with immune receptors and effectors involved in pathogen recognition and control. Recent advances in molluskpathogen interactions have shown the existence of highly diverse somatically generated receptors that give high specificity to pathogen recognition (16,17). So far, in oysters, recognition is mediated by germ-line encoded receptors, such as a β-integrin, involved in hemocyte phagocytosis (18); it was proposed to serve as a receptor for the major plasma protein, the extracellular superoxide dismutase Cg-EcSOD, which contains a RGD cellbinding domain (19).…”
mentioning
confidence: 99%
“…Its potential role in the context of immune evasion strategy has been previously discussed (DeMarco et al 2010). It is of particular interest that MEG-2 shares many common features with the SmPoMuc genes, previously described as major molecular determinants for the compatibility polymorphism (Roger et al 2008b). SmPoMuc genes encode highly polymorphic glycosylated proteins that are secreted in miracidia and their cDNA variants seem to be generated by the "pick and mix" strategy as described for the MEG genes (Berriman et al 2009).…”
Section: Discussionmentioning
confidence: 97%